Sepsis : la otra cara de la respuesta inmune (2011)
ABSTRACT: Worldwide, sepsis continues to be a major cause of death, in spite of the impressive advances in its research. This condition represents an imbalance in the different immunological mechanisms responsible for neutralizing the infectious agent invasion. In this paper, a review of the physiopathological concepts of sepsis is presented, including the different genetic variations which make an individual susceptible to sepsis.